2021
DOI: 10.1371/journal.pone.0252859
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis serotype and synthetic disease-modifying anti-rheumatic drugs in patients with periodontitis: A case-control study

Abstract: Patients with rheumatoid arthritis (RA) experience a higher prevalence of periodontitis. This study aimed to examine the variation of periodontitis experienced with different serotypes suffered by RA patients and to examine the relationship between the different medications taken for RA that may influence this relationship. Two hundred and sixty RA and control participants underwent standardized periodontal examinations. Medical, serological and radiological (Sharp/van der Heijde) records were assessed. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In animal models, oral inoculation of Porphyromonas gingivalis was found to exacerbate arthritis through the increased production of IL-17 25 . Therefore, periodontitis may also be important in the patients with already stablished rheumatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, oral inoculation of Porphyromonas gingivalis was found to exacerbate arthritis through the increased production of IL-17 25 . Therefore, periodontitis may also be important in the patients with already stablished rheumatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…RA treatment may influence periodontitis; it has been described that the use of anti-IL-6 is associated with improvement in the gingival index, bleeding on probing, probing depth, and clinical attachment level 25 . Improvement in periodontal health with anti-TNF therapy and Jak inhibitors such as tofacitinib are also observed 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Nik-Azis N.M. et al compared two groups of patients with periodontitis, the first with RA and the second with osteoarthritis. They observed that MTX in monotherapy reduction in PD at 3 months, compared with MTX in combination with SSZ and HCQ [73].…”
Section: The Effect Of Anti-rheumatic Drugs On Periodontal Diseasementioning
confidence: 99%
“…Another study concluded that citrulline levels in saliva are not associated with the severity of RA disease, despite significant differences in their periodontal status [17]. Other studies link these diseases since the treatment stage with specific medications for RA, as well as with the way in which these are associated with some periodontal health parameters, and how they can affect the periodontal health of this group of patients [18]. Moreover, they indicate that non-surgical periodontal therapy has a beneficial effect on the signs and symptoms of RA, regardless of the medications used to treat this condition [19].…”
Section: Introductionmentioning
confidence: 99%